Feasible use of rock oyster (Crassostrea commercialis) and seaweeds (Gracilaria salicornia and Caulerpa lentillife) as biofilter in a laboratory - scale closed recirculating system for juveniles spotted babylon (Babylonia areolata) - Chaitanawisuti, Nilnaj; Santhaweesuk, Wannanee; Kritsanapuntu, Sirusa (Journal of Research in Biology, 2011)
This study was conducted to assess the feasible use of rock oyster (Crassostrea commercialis) in biofiltration and two seaweeds (Gracilaria salicornia and Caulerpa lentillife) as nutrient absorbant in a laboratory - scale recirculating system for growing of juveniles spotted babylon (Babylonia areolata). The experiment was carried out in triplicates over a period of 90 days. The experiment was a complete randomized design with three growth trials: Treatments 1: without oyster and seaweed biofilter used as a control; Treatment 2: Oyster biofiltration (1,500 g per tank) and seaweed (G. salicornia) absorption (250 g per tank); and Treatment 3: Oyster biofiltration (1,500 g per tank) and seaweed (C. lentillife)absorption (250 g per tank). No significant differences (P>0.05) in final shell length, final body weight, body weight gains, shell length increment and growth rate among all treatments. Growth rate in shell length and body weight of spotted babylon ranged from 0.33 – 0.34 cm mo-1 and 0.62 – 0.67 g mo-1, respectively. Significant differences (P<0.05) in final survival rate of spotted babylon were found among treatments, ranging from 86.72 to 86.98 % compared with those of the control (84.27%). There were no significant differences (P>0.05) in water temperature, salinity, pH, dissolved oxygen, ammonia-nitrogen, nitrite-nitrogen, nitrate-nitrogen and phosphate-phosphorus among the growth trials but not for alkalinity. This study can conclude that G. salicorni and C. lentillifera can be used as nutrient biofilter for regulating of water quality in a closed recirculating system for growing juveniles spotted babylon but not suitable on using oyster.